Forecasting Of Load-Carrying Ability of the Earth File around Of Horizontal Cavities (Global Journal of Human-Social Science, 2012)
The scattered destruction of a heavy half-plane with a circular hole under an operation of internal constant pressure is investigated On a rectilinear side a border of the half-plane is under load The Suvorov-Akhundov s theory on isotropic bodies damage is used In chosen final investigated area a numerical way of the solution is used and border conditions in infinity were transferred on it Lateral pressure coefficient three values illustrations on time of development of the destroyed area are given
Keywords: Destruction; tunnels; deformation; stress